Oleaginous microorganisms as sustainable feedstock for biodiesel production - Raposo, Sara (2014)
Biodiesel has had a considerable development in the past decade. High cost of oil feedstocks and problems associated with extensive cultivation of oleaginous plants to face growing market demand, competing with the agro-food industry for agricultural resources have limited production development. This situation has raised an intense global I&D effort in the search for raw materials alternative to oleaginous plants, which are the main energy resource for biodiesel production. Promising results have been obtained with oleaginous microorganisms, Rhodosporidium toruloides and Yarrowia lipolytica, being one of the potential sources of oils for biodiesel production.